Best article 2022 and some updates and announcements on The Journal of Agricultural Education and Extension - Klerkx, Laurens; Davis, Kristin E. (Informa UK Limited, 2023)
With the publication of this first issue of 2023, it is a good moment to look back and to look ahead. Looking back, 2022 has been another good year for The Journal of Agricultural Education and Extension (JAEE), in which we managed to publish a variety of interesting articles spanning the range of topics outlined in JAEE’s aims and scope. After a spike in 2020 and 2021, the total number of submissions has stabilized again, but there is a continuous flow of accepted papers that quickly are published online before being included in an issue.